Perancangan Tempat Sampah Meja Otomatis Berbasis Arduino Uno dengan Fitur Suara - Darmawan, E; Fathurohman, I (Jurnal MESIL (Mesin Elektro Sipil), 2025)
The presence of rubbish scattered around the house has an impact on health. The presence of scattered rubbish can trigger the residence of pests such as cockroaches, mosquitoes, ants and flies. The presence of pests in the house can spread disease and poisoning. In this study, researchers created a trash can that can open the lid automatically. The aim is so that people who throw away rubbish do not need to open the lid of the rubbish bin so that the rubbish thrower doesn't get dirt stuck to the rubbish bin cover. This tool uses electronic components including an Arduino Uno microcontroller, ultrasonic sensor, servo motor and speaker. In this automation system, the movement of opening and closing the cover and speaker is controlled by the distance value of the obstacle. The trash can cover will open if the obstacle distance is below or equal to 5 cm. The ultrasonic sensor reads the distance value of the obstacle which triggers the movement of opening and closing the trash can drive by a servo motor and sound by a speaker. The Arduino Uno microcontroller is used as a device interaction link. Based on the results of testing three times for obstacles on the ultrasonic sensor, it was found that the distance between the test results on the device was not the same as the distance from the results using a ruler. The error percentage from three tests is between 3.6% to 6%. The average error percentage results are 6%. Meanwhile, the automation system for making this tool runs in accordance with the tool design the trash can lid.